2005
DOI: 10.1253/circj.69.131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Endothelin Receptor Antagonist Bosentan on Hemodynamics, Symptoms and Functional Capacity in Japanese Patients With Severe Pulmonary Hypertension

Abstract: ulmonary arterial hypertension (PAH) is a rare and debilitating disease, characterized by an increase in pulmonary vascular resistance that ultimately leads to right heart failure and death. 1 When a definite cause can not be demonstrated, the condition is termed primary pulmonary hypertension (PPH), which predominantly affects women most commonly in their third decade of life. 2 No ethnic predisposition is apparent in the National Institutes of Health registry, and the proportions by ethnic group parallel tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Since lesions are observed in most of the pulmonary vascular system from the tunica intima and media to the adventitia, conventional vasodilators are only effective for the systemic vasculature and show almost no effect on the pulmonary vasculature. The only formulation which shows evidence of exerting a pulmonary vasodilator effect during the chronic period is an endothelin receptor antagonist [25][26][27][28][29][30][31][32][33][34] apart from prostacyclin 22,[35][36][37][38][39][40] and its derivatives. [15][16][17][18]41,42) The 6MW distance is widely used as an indicator of the functional severity of pulmonary hypertension in each individual as a clinical test for efficacy evaluation before and after administration of several pulmonary vasodilators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since lesions are observed in most of the pulmonary vascular system from the tunica intima and media to the adventitia, conventional vasodilators are only effective for the systemic vasculature and show almost no effect on the pulmonary vasculature. The only formulation which shows evidence of exerting a pulmonary vasodilator effect during the chronic period is an endothelin receptor antagonist [25][26][27][28][29][30][31][32][33][34] apart from prostacyclin 22,[35][36][37][38][39][40] and its derivatives. [15][16][17][18]41,42) The 6MW distance is widely used as an indicator of the functional severity of pulmonary hypertension in each individual as a clinical test for efficacy evaluation before and after administration of several pulmonary vasodilators.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study was designed with an administration period set at 12 weeks, similar to other clinical studies of PAH therapy such as intravenous epoprestenol, 22) oral bosentan, 32) and sildenafil. 43) During continuous long-term therapy with conventional beraprost, a decrease in the extent of the increase in the 6MW distance was reported from 3 months to 12 months during administration to patients with PAH.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that bosentan administration results in an improvement in a 6-minute walk after 4 weeks. 9,14) It is natural to attribute these effects to this endothelin receptor blocker, because no other conditions were changed in the 4 weeks of treatment. Although hemodynamic data were compared after 12 weeks in other studies, 9,14) we observed a hemodynamic improvement with bosentan even after 4 weeks and further improvement in pressure gradient of TR by echocardiography.…”
Section: )mentioning
confidence: 99%
“…7,8) Meanwhile, a dual endothelin receptor antagonist, bosentan, has been available in Japan since 2005. 9) We report a case of IPAH in which repetitive syncope was successfully treated by bosentan. Syncopal attack in this patient was thought to be related mainly to PH and partially to hemodialysis and mild aortic stenosis.…”
mentioning
confidence: 99%
“…Current treatment algorithms recommend prostanoid analogs (iloprost, treprostinil), bosentan, sildenafil, and epoprostenol (EPO), depending on disease severity. 1,2 Although each of these drugs has been reported to improve hemodynamics and exercise capacity in PAH patients, [3][4][5][6][7][8][9][10][11][12][13][14][15] improvement of long-term survival in patients with idiopathic PAH (IPAH) has been achieved only with EPO, 4-6 treprostinil 13 and bosentan. 10 PAH is a complex disease with multifactorial pathophysiology.…”
mentioning
confidence: 99%